Convergence, capital accumulation and the nominal exchange rate - Péter Benczúr; István Kónya (Magyar Nemzeti Bank, 2007)
This paper develops a flexible price, two-sector nominal growth model, in order to study the role of the exchange rate regime in capital accumulation (convergence). We adopt a standard model of a small open economy with traded and nontraded goods, and enrich its structure with costly investment and a preference for real money holdings. We find that (i) the choice of exchange rate regime influences the transition dynamics of a small open economy, (ii) a one-sector model does not adequately capture the channels through which the nominal side interacts with real variables, and (iii) as a consequence, sectoral asymmetries are important for understanding the effects of the exchange rate regime on capital accumulation.
Keywords: F32; F41; F43; 330; two-sector growth model; small open economy; capital accumulation; household portfolios; real effects of nominal shocks; Kleine offene Volkswirtschaft; Investition; Wechselkurs; Wechselkurssystem; Wachstumstheorie